The influence of functional skewness on prognosis of cancer of mammary gland - L. E. Erendeeva; M. V. Zavyalova; E. M. Slonimskaya; V. M. Perelmuter (Бюллетень сибирской медицины, 2002)
In this study the features of developing cancer both in the left and right breast have been compared. We examined 45 parameters which characterize clinical as dell as morphological features of breast cancer. Of all parameters investigated only 5 are more informative ones. They show that breast cancer is developing differently in the right and the left breast. We conclude that localization of cancer in the right breast has a worse prognosis. The results obtained are discussed.